2006
DOI: 10.1080/00365520600575688
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac autonomic regulation differentiates reflux disease with and without erosive esophagitis

Abstract: Patients with ERD and NERD display a similar degree of symptom severity, but the pattern of autonomic function appears to differ between NERD and ERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
0
22
0
1
Order By: Relevance
“…Autonomic function might be deranged in patients with reflux disease also; indeed, autonomic dysfunction has been reported in patients with reflux disease [61], but it has not been investigated in subset of patients with BE. Of course, the present study does not permit identification of the exact gastroduodenal motor events that result in an increased duodenogastroesophageal reflux in patients with BE; this would require a separate study of the measurement of gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic function might be deranged in patients with reflux disease also; indeed, autonomic dysfunction has been reported in patients with reflux disease [61], but it has not been investigated in subset of patients with BE. Of course, the present study does not permit identification of the exact gastroduodenal motor events that result in an increased duodenogastroesophageal reflux in patients with BE; this would require a separate study of the measurement of gastric emptying.…”
Section: Discussionmentioning
confidence: 99%
“…It seems also unlikely that differences between the GORD and control groups regarding gender distribution could have influenced our results, since the increased proportion of women among patients would be associated with decreased antral contractility, as demonstrated in another scintigraphy study 20 . Another possibility is that increased amplitude of antral contractions might be caused by diminished inhibition of antral motor activity secondary to autonomic dysfunction, which has been suggested as occurring in GORD patients 34,35 . Disturbed relaxation of the proximal stomach in response to a meal, which has been demonstrated in GORD, 7–11 could also be involved in the origin of increased antral contractility, as distension of the gastric fundus can enhance or inhibit antral contractility through gastro‐gastric reflexes 36,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic abnormalities have been reported in both ERD and NERD patients [54, 55]. A study by Shapiro et al [32] found no differences in baseline autonomic function between functional heartburn and NERD patients.…”
Section: Disease Assessment For Nerd Studiesmentioning
confidence: 99%